2020
DOI: 10.4067/s0718-50732020000200111
|View full text |Cite
|
Sign up to set email alerts
|

Modelación basada en agentes:

Abstract: Construction projects represent complex systems where the interactions between the multiple project resources and stakeholders change over time; however, traditional methods to manage construction projects typically cannot capture such complexity in its totality. Thus, limiting our understanding of such complexity on construction projects. A novel approach used to investigate complex adaptive systems, Agent-based modeling (ABM), allows modeling the interaction between multiple agents that leads to emergent beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Liang et al (2018) stated that the ABM method can help to clearly describe the construction process, subjects and complex variables of projects, and it can also solve the dynamic and uncertain problems caused by the constraints of basic factors such as time and space in a construction system. Araya (2020) found that the ABM method can effectively portray agents who can learn independently and produce adaptive behaviors to the changes in projects. Araya (2021) stated that ABM can effectively model the interaction process of relevant elements in the construction of complex system, simulate the entire evolution process of the system, and test the effects of policies and interventions on various scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al (2018) stated that the ABM method can help to clearly describe the construction process, subjects and complex variables of projects, and it can also solve the dynamic and uncertain problems caused by the constraints of basic factors such as time and space in a construction system. Araya (2020) found that the ABM method can effectively portray agents who can learn independently and produce adaptive behaviors to the changes in projects. Araya (2021) stated that ABM can effectively model the interaction process of relevant elements in the construction of complex system, simulate the entire evolution process of the system, and test the effects of policies and interventions on various scenarios.…”
Section: Introductionmentioning
confidence: 99%